Primary amyloidosis of the urinary bladder: A case report - N Srinath; A S Sandhu; R Bharadwaj; R Sood; S K Gupta; A A Pradhan; P Madhusoodanan (Indian Journal of Urology, 2003)
A case of young woman with primary bladder amyloido-sis presenting with haematuria is reported. The diagnosis was confirmed by bladder biopsy. Secondary amyloido-sis was excluded after extensive search for underlying causes. This rare entity can usually be treated conserva-tively. Long-term follow-up is recommended.